2009
DOI: 10.1007/s00382-009-0688-3
|View full text |Cite
|
Sign up to set email alerts
|

The boreal spring variability of the Intra-Americas low-level jet and its relation with precipitation and tornadoes in the eastern United States

Abstract: The Intra-Americas Sea (IAS) low-level jet has been studied mainly for the summer and winter seasons. In contrast, spring conditions have been studied less. Here we analyze the boreal spring variability of the IAS low-level jet (IA-LLJ) and its relation with precipitation and tornadic activity in the region of the lower Mississippi, Tennessee and Ohio River basins (MORB). The main mode of variability of the spring IA-LLJ is obtained from a combined principal component analysis of zonal and meridional winds at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 36 publications
6
40
2
Order By: Relevance
“…These results are consistent with those of Cook and Schaefer (2008), who found that tornado activity in La Niña and neutral phases were more frequent in the entire continental United States from January to March 1950March -2003. These results are also consistent with the results of Muñoz and Enfield (2011) and Kellner and Niyogi (2014) despite the more limited regional scope addressed in each of those investigations.…”
Section: Possible Influences Of Enso On the Climatology Of January-apsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are consistent with those of Cook and Schaefer (2008), who found that tornado activity in La Niña and neutral phases were more frequent in the entire continental United States from January to March 1950March -2003. These results are also consistent with the results of Muñoz and Enfield (2011) and Kellner and Niyogi (2014) despite the more limited regional scope addressed in each of those investigations.…”
Section: Possible Influences Of Enso On the Climatology Of January-apsupporting
confidence: 82%
“…This approach does not suffer from a failure to distinguish between actual tornado events and the occasional false alarms that occur with the use of environmental severe weather indices. 3) It will include tornado outbreaks dating back to 1950 so as to provide a basis for a more robust atmospheric climatology in this study when compared with that of Allen et al (2015) (who employed data only back to 1979) and other previous studies (Muñoz and Enfield 2011;Lee et al 2013;Barrett and Gensini 2013). …”
Section: Januarymentioning
confidence: 99%
See 1 more Smart Citation
“…The current understanding of the Caribbean atmospheric circulation is based on the characteristics of the North Atlantic subtropical High (NAH) and its related features including the north-east trade winds and the Caribbean Low Level Jet (CLLJ). Previous investigations have related the direct influence of these features of Caribbean atmospheric circulation to rainfall characteristics on annual, seasonal, and monthly scales (Amador 2008;Hastenrath 1976;Hastenrath and Lamb 1977;Muñoz et al 2008;Muñoz and Enfield 2011;Wang 2007;Wang and Lee 2007;Cook and Vizy 2010), and have investigated the influence of other major factors such as Atlantic and Pacific sea surface temperatures (SSTs), the El Niño-Southern Abstract The day-to-day variability of the atmospheric circulation over the Caribbean region is investigated in this work through the extraction of frequently occurring atmospheric circulation types. A two-stage cluster analysis technique using Ward's agglomerative algorithm followed by the k-means algorithm was applied to daily circulation defined by the NCEP/DOE reanalysis wind components at the 850 hPa level for the period 1979-2010.…”
Section: Introductionmentioning
confidence: 99%
“…The CLLJ, a sub-regional feature also known as the Intra-America Seas low-level jet (Amador 2008), is a localized feature of the atmospheric circulation in the Caribbean with an east-west axis located in the Caribbean Sea near 15°N (Amador 2008) between northern South America and the Greater Antilles islands. The CLLJ transports moisture from the tropical Atlantic into the Caribbean Sea, Gulf of Mexico, and influences rainfall in the United States (Gamble and Curtis 2008;Wang 2007;Amador 2008;Cook and Vizy 2010;Muñoz and Enfield 2011). The CLLJ exhibits maximum wind speeds at the 925 hPa level with wind speeds up to 16 m/s (Amador 2008; Whyte et al 2008) while wind speeds at the 10 m level are between 8 and 10 m/s (Chadee and Clarke 2014).…”
Section: Introductionmentioning
confidence: 99%